Resolution of congenital nasolacrimal duct obstruction with conservative management - Shrestha, J B (Journal of Chitwan Medical College, 2017)
Congenital nasolacrimal duct obstruction is the commonly encountered congenital anomaly in pediatric population occurring in as many as 30% of new borns. Conservative management of such condition with topical antibiotics and properly performed massage of the nasolacrimal sac is appropriate treatment during the first few months of age. The purpose of this study was to determine the rate of resolution of nasolacrimal duct obstruction with conservative management in infants up to 10 months of age. A total of 181 infants of age up to 10 months old with the diagnosis of Congenital nasolacrimal duct obstruction were advised nasolacrimal duct massage with or without the prescription of topical antibiotics. Resolution of nasolacrimal duct obstruction was assessed at 3 month and 6 month and was defined as the absence of all clinical signs of nasolacrimal duct obstruction. At the 6-month examination, 163 eyes (83%) of 181 children showed resolution with conservative management. The overall success rate of Congenital nasolacrimal duct obstruction with conservative management was high and this form of management can be considered as one of the best options in infants.